Cantonese versus Canadian Evaluation of Directive and Non-Directive Therapy - Waxer, Peter H. (Canadian Journal of Counselling and Psychotherapy, 2011)
Cantonese and Canadian university students were asked to read transcripts and Albert Ellis counselling "Gloria" from the film "Three Approaches to Psychotherapy" and then rate these counsellors on the dimensions of directiveness, forcefulness, repetitiveness, sensitivity, politeness and willingness to see either Ellis or Rogers. Results indicated Canadians were more willing to see Rogers than were Chinese students, in spite of parallels between spoken Cantonese and Rogers' reiterative style. Chinese students were less condemning of Ellis' directive style than were Canadian students. These results are consistent with prior studies suggesting Asian clientele view counselling as a more directive, paternalistic and autocratic process, in contrast to North Americans who see counselling as a more explorative and democratic process.